Engagement Factors in Social Media Marketing on Instagram: A Case Study of Parasteh Gallery - Ahmadi, Yousef (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In today's extremely competitive market, companies and businesses are seeking for new strategies to raise consumer awareness and strengthen their brand. Social media is one of these strategies, and it has transformed the sphere of business and digital marketing. The objective of this research is to find out how the content vividness and content type affect customers brand loyalty on social media. The study of Verschueren (2017) and Mafe et al. (2014) served as the foundation for the research model. The study's statistical population includes all Instagram followers of Parasteh Gold Gallery. 404 followers were surveyed in order to obtain data using the available sampling method. A questionnaire was used to collect data, which was then analyzed using structural equation modeling and SPSS 18 and LISREL software. The findings revealed that the vividness of content have a substantial impact on customer attitudes toward the brand, customer attitudes toward the content, and brand engagement. Furthermore, the content type has an impact on customer attitudes toward brand, content, and brand engagement. Finally, customer attitudes toward the brand, customer attitudes toward content, and customer engagement all have a significant influence on brand loyalty.

ÖZ: Günümüzün son derece rekabetçi pazarında şirketler ve işletmeler, tüketici bilincini artırmak ve markalarını güçlendirmek için yeni stratejiler aramaktadır. Sosyal medya bu stratejilerden birisidir ve iş ve dijital pazarlama alanını dönüştürmüştür. Bu araştırmanın amacı, içerik canlılığının ve içerik türünün müşterilerin sosyal medyadaki marka sadakatini nasıl etkilediğini bulmaktır. Verschueren (2017) ve Mafe ve ark. (2014) araştırma modelinin temelini oluşturmuştur. Çalışmanın istatistiksel popülasyonu, Parasteh Gold Gallery'nin tüm Instagram takipçilerini içermektedir. Mevcut örnekleme yöntemi kullanılarak veri elde etmek için 404 takipçi ile anket yapılmıştır. Bu anket daha sonra yapısal eşitlik modellemesi ve SPSS 18 ve LISREL yazılımı kullanılarak analiz edildi. Bulgular, Sosyal medya içerik canlılığının markaya yönelik müşteri tutumları, içeriğe yönelik müşteri tutumları ve marka bağlılığı üzerinde önemli bir etkiye sahip olduğunu ortaya koydu. Ayrıca, içerik türünün markaya, içeriğe ve marka bağlılığına yönelik müşteri tutumları üzerinde etkisi olduğunu gösterdi. Son olarak, markaya yönelik müşteri tutumları, içeriğe yönelik müşteri tutumları ve müşteri katılımı, marka sadakati üzerinde önemli bir etkiye sahip Olduğunu ortaya arkardı.
Master of Arts in Marketing Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2021. Supervisor: Prof. Dr. Mehmet Haluk Köksal.
Keywords: Business Administration Department; Marketing Management; Internet marketing; Social Media--Online marketing--Management; Consumer Behavior, Content Vividness, Content Type, Social Media, Customers’ Attitude, Brand Loyalty